INFLUENCE OF PSYCHOLOGICAL CAPITAL OF EMPLOYEES IN TECHNOLOGY ENTERPRISES AT GUANGDONG IN CHINA - Bhaumik, Amiya (International Journal of Psychosocial Rehabilitation, 2020)
The acquisition and maintenance of their competitive advantages is a subject that corporate managers, academic researchers who care about corporate management, and even government departments should be faced.People have to pay attention to the positive, stateful, and developable psychological elements that employees exhibit in the working environment, growth and development process. This psychological factor has input-output characteristics, which is conducive to the improvement of individual work performance and meets the Psychological Resources criteria for active organizational behavior. Thereby helping companies gain new competitive advantages. On this basis, I used strict item screening procedures and project analysis methods, EFA, CFA and other quantitative means, innovatively obtained the high-level structure of five-dimensional psychological capital which is Hope, Optimism, Resilience, Authenticity and Forgiveness of the employees in Guangdong Technology enterprises.The structure was further validated in the following 432 valid samples of 43 technology companies in Guangdong Province. The results show that the five-dimensional high-order psychological capital structure has good discriminant validity and convergence validity, and its reliability coefficient reaches the psychological measurement standard.